2014
DOI: 10.1007/s12149-014-0912-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in PET/CT image quality in overweight patients with PSF and TOF

Abstract: ObjectiveThe aim of this study was to evaluate the effect of the point spread function (PSF) and time of flight (TOF) on PET/CT images of overweight patients in relation to the iteration number and the acquisition time.MethodsThis study consisted of a phantom study and a clinical study. The NEMA IEC body phantom and a 40 cm diameter large phantom (LG phantom) simulating an overweight patient were used in this study. Both phantoms were filled with 18F solution with a sphere to background ratio of 4:1. The PET d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…This study did not take the subject size into consideration. However, the PET image quality of overweight subjects (body mass index $ 25) is degraded because of an increase in statistical noise (29)(30)(31). To obtain sufficient image quality, adjusting the injection activity or scanning time in each patient based on body weight or body mass index (29,32,33) might be required for overweight subjects (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…This study did not take the subject size into consideration. However, the PET image quality of overweight subjects (body mass index $ 25) is degraded because of an increase in statistical noise (29)(30)(31). To obtain sufficient image quality, adjusting the injection activity or scanning time in each patient based on body weight or body mass index (29,32,33) might be required for overweight subjects (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The highest SNR was attained in images reconstructed with OSEM + PSF + TOF. This method of reconstruction was thus found to improve the image quality for overweight patients [9]. Although image quality is improved, clinical usefulness of images depends on lesion detectability, and the research does not indicate that improved image quality due to PSF and TOF translates into clinical usefulness.…”
Section: Potential Of Tof and Psf In Patient Dose Administration Basementioning
confidence: 92%
“…3D PET reconstruction with PSF modeling shows on by 45% and contrast On the same hand, comparison of PSF with PSF images showed a mean bias up to 12% for 8% for SUVmean, and 7,5% for SUVpeak [8]. In addition, it has been shown that, combined with the OSEM algorithms, image quality, especially for overweight patients, could be TOF [5,9]. Armstrong et.al.…”
Section: In Pet Medicalmentioning
confidence: 99%
See 1 more Smart Citation
“…And, they gave the assumption that the degradation function of CT system has Gaussian distribution. Multiple sets of bone interfaces and the iterative strategy [4][5][6] were utilized to estimate the point spread function. Blind equalization algorithm was applied to the two-dimensional CT blind image restoration [7][8][9].…”
Section: Introductionmentioning
confidence: 99%